CORE learning model: Its effectiveness towards students’ creative thinking - Antomi Saregar; Umi Nur Cahyanti; Misbah Misbah; Nur Endah Susilowati; Adyt Anugrah; Nurlaela Muhammad (Institute of Advanced Engineering and Science, 2021)
The research has been carried out at the Islamic junior high school of East Lampung to determine the effectiveness of the Connecting, Organizing, Reflecting, and Extending (CORE) learning model on students’ creative thinking skills on sound waves topic. The research method used was a quasi-experimental design with Non-Equivalent Control Group Design. Data on creative thinking skill were collected using essay test instrument. This research was conducted on the eighth-grade students of an Islamic senior high school in East Lampung with a sample of 60 students taken by using purposive sampling technique. Based on the Effect Size test, the effectiveness value of the CORE model on students’ creative thinking skills are 0.48 which is in the medium category. These results prove that the CORE learning model is effective in enhancing students’ creative thinking skills on sound wave material. This study also provides a storyboard on how to apply an effective CORE model to improve students’ creative thinking abilities.